Research on creep characteristics of loading and unloading of hard Flint limestone - Yan, Qiao; Qin, Shifu; Sang, Xuefeng; Luo, Zuosen; Liang, Minghao (Frontiers in Materials, 2023)
The hard Flint limestone of Shuibuya hydropower station underground construction cavern is utilized as a research object to investigate the creep problem caused by excavation of rock masses such as caverns. In order to perform a triaxial compression grade-unloading creep test, the actual adjustment path of stress during excavation of underground cavern surrounding rock is used. Limestone under different confistiff pressures is then evaluated. Based on the Nishihara model, the elastic damage element considering time-dependent damage is introduced, and the unloading creep constitutive model of stiff Flint limestone is established and verified by experiments. The results show: (1) Deformation and creep strain appear at all stress levels. (2) As the unloading amount increased from 2 MPa to 4 MPa, the quasi-destructive stresses of the samples were smaller from 83 MPa to 79 MPa, indicating that the unloading amount affected the final creep damage strength of the rock samples. In other words, the higher the unloading amount, the lower the ultimate creep failure strength. (3) When entering the accelerated creep stage, the axial and lateral creep strains of the sample increase nonlinearly, and the rupture duration of the sample is very short. Therefore, the creep deformation and creep rate characteristics of this stage should be paid attention to in practical engineering. (4) Different from the loading stress path, the failure mode of the Flint limestone rock sample is different. When the unloading amount is 2 MPa and 4 MPa, the creep failure mode of the Flint limestone rock sample is shear failure, showing a significant oblique section crack. (5) The nonlinear creep model curve of aging damage and the fitting effect of the unloading creep test curve are acceptable. The rationality of the established nonlinear creep model is illustrated.